Floral biology and physicochemical characterization of wild passion fruit Passiflora setacea d.C BRS Pérola do Cerrado cultivated in the state of Rio de Janeiro - Ivan Marcos Rangel Junior; Marco Antonio da Silva Vasconcellos; Raul Castro Carriello Rosa; Fabio Ferreira Cruvinel (Revista Brasileira de Fruticultura, 2018)
Abstract This work aimed to evaluate the floral and physicochemical characteristics of passion fruits BRS Pérola do Cerrado cultivar (Passiflora setacea D.C.), as well as its relationship with local climatic factors. Peak flowering, time in days of floral appearance until anthesis and until fruits harvest, floral morphometry, time of flower opening and closing, occurrence of natural self-pollination, geitonogamy and floral incompatibility, physicochemical characteristics of fruits and relationship with climatic variables were evaluated. Under the conditions of this study, it was observed that the flowering peak occurred in November and the time of flower opening ranged from 7:21 pm to 8:40 pm throughout the year, probably influenced by daily solar radiation; while the time of flower closing occurred between 6:00 am and 8:00 pm. After closing, flowers showed no recurrence of floral opening. Flowers of Passiflora setacea species BRS Pérola do Cerrado cultivar are self-incompatible and do not allow geitonogamy. Therefore, for fruit formation, cross-pollination is necessary. Regarding fruit setting in the different pollination methods, rates were 34.6% when artificially made and 53.5% in case of natural pollination. Fruits had, on average, longitudinal diameter of 4.9 cm, cross-sectional diameter of 46 mm and fresh mass of 55 g, juice volume of 15.7 ml per fruit, 13.31 ° Brix and total titratable acidity of 1.7 g / 100g ac. citric.